The Implementation of Technology-Based Media in Improving English Speaking Skill of Hospitality Students in Mataram Tourism College - Sri Wahyuningsih; Ida Nyoman Tri Darma Putra (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2020)
This research aims to find out the effectiveness of the application of technology-based teaching media to improve the speaking skills of the Hospitality Study Program Students of STP Mataram. In this study, several media that utilize computers and the internet will be used in learning speaking. The use of the application Rosetta Stone, Duolingo, and YouTube videos integrated with the google classroom are used as learning media for students' speaking learning of the hospitality study program students. In this study, 30 students are used as the experimental group and 30 students as a controlled group. The results of this study indicated that the value of t-test > t table (3.462> 2.676), which means that there is a significant difference in English speaking skills using technology-based learning media. In conclusion, the use of technology-based learning media is effective in enhancing students’ speaking skill.